Dealing with data gaps for TianQin with massive black hole binary signal - Lu Wang; Hong-Yu Chen; Xiangyu Lyu; En-Kun Li; Yi-Ming Hu (European Physical Journal C: Particles and Fields)
Abstract Space-borne gravitational wave detectors like TianQin might encounter data gaps due to factors like micro-meteoroid collisions or hardware failures. Such events will cause discontinuity in the data, presenting challenges to the data analysis for TianQin, especially for massive black hole binary mergers. Since the signal-to-noise ratio (SNR) accumulates in a non-linear way, a gap near the merger could lead to a significant loss of SNR. It could introduce bias in the estimate of noise properties, and the results of the parameter estimation. In this work, using simulated TianQin data with injected a massive black hole binary merger, we study the window function method, and for the first time, the inpainting method to cope with the data gap, and an iterative estimate scheme is designed to properly estimate the noise spectrum. We find that both methods can properly estimate noise and signal parameters. The easy-to-implement window function method can already perform well, except that it will sacrifice some SNR due to the adoption of the window. The inpainting method is slower, but it can minimize the impact of the data gap.